2022
DOI: 10.3390/ijms23094509
|View full text |Cite
|
Sign up to set email alerts
|

Human α-Defensin-6 Neutralizes Clostridioides difficile Toxins TcdA and TcdB by Direct Binding

Abstract: Rising incidences and mortalities have drawn attention to Clostridioides difficile infections (CDIs) in recent years. The main virulence factors of this bacterium are the exotoxins TcdA and TcdB, which glucosylate Rho-GTPases and thereby inhibit Rho/actin-mediated processes in cells. This results in cell rounding, gut barrier disruption and characteristic clinical symptoms. So far, treatment of CDIs is limited and mainly restricted to some antibiotics, often leading to a vicious circle of antibiotic-induced di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The growing mechanistic knowledge about the biology of C. difficile toxins has led to novel anti-toxin approaches, which might be useful in the future as supportive treatment options against C. difficile -associated diseases and/or post-traumatic complications. For instance, body-own antimicrobial peptides, such as certain defensins, were shown to inhibit TcdA/B and CDT either by direct interaction and formation of biologically inactive aggregates (Fischer et al 2020 ; Korbmacher et al 2020 ; Barthold et al 2022 ) or by inhibiting enzyme activities, as suggested for human α-defensin and TcdB (Giesemann et al 2008 ).…”
Section: Role Of Bacterial Toxins In Traumatic Diseases Barrier Failu...mentioning
confidence: 99%
“…The growing mechanistic knowledge about the biology of C. difficile toxins has led to novel anti-toxin approaches, which might be useful in the future as supportive treatment options against C. difficile -associated diseases and/or post-traumatic complications. For instance, body-own antimicrobial peptides, such as certain defensins, were shown to inhibit TcdA/B and CDT either by direct interaction and formation of biologically inactive aggregates (Fischer et al 2020 ; Korbmacher et al 2020 ; Barthold et al 2022 ) or by inhibiting enzyme activities, as suggested for human α-defensin and TcdB (Giesemann et al 2008 ).…”
Section: Role Of Bacterial Toxins In Traumatic Diseases Barrier Failu...mentioning
confidence: 99%